RAVE as a Gaia precursor: what to expect from the Gaia RVS?. Issue 67 (17th July 2015) - Steinmetz, M.
Abstract : The Radial Velocity Experiment (RAVE) is a large wide-field spectroscopic stellar survey of the Milky Way. Over the period 2003-2013, 574, 630 spectra for 483, 330 stars have been amassed at a resolution of R=7500 in the Ca-triplet region of 8410–8795 Å. Wavelength coverage and resolution are thus comparable to that anticipated from the Gaia RVS. Derived data products of RAVE include radial velocities, stellar parameters, chemicals abundances for Mg, Al, Si, Ca, Ti, Fe, and Ni, and absorption measures based on the diffuse interstellar bands (DIB) at 8620 Å. Since more than 290 000 RAVE targets are drawn from the Tycho-2 catalogue, RAVE will be an interesting prototype for the anticipated full Gaia data releases, in particular when combined with the early Gaia data releases, which contain astrometry but not yet stellar parameters and abundances.